Does foreign banks entry fosters bank efficiency? Empirical evidence from Malaysia - Sufian, Fadzlan; Habibullah, Muzafar Shah (Kauno Technologijos Universitetas, Kaunas University of Technology, 2010)
The impact of foreign banks entry on the banking sector has been well documented in the literature. However, these studies have been confined to the conventional banking sector. On the other hand, virtually nothing has been published in respect to the impact of foreign banks entry on the Islamic banking sector. The purpose of the present paper is to provide new empirical evidence on the impact of foreign banks entry on the efficiency of the incumbent domestic and foreign Islamic banks. Although there exist several other studies which have examined the performance of the Malaysian Islamic banking sector (e.g. Samad, 1999; Samad and Hassan, 2000; Sufian, 2007; Mokhtar et al. 2008, Majid et al. 2009, and others), the focus of these studies have not been the impact of foreign banks entry. The present study therefore attempts to fill in the gap and add insights to the present literature in several respects as follows: First, by employing the Data Envelopment Analysis (DEA) method, we examine whether the De Novo foreign Islamic banks are relatively more efficient than the incumbent domestic and foreign Islamic banks. To date, empirical evidence form the contemporary banking industry has mainly suggested that foreign banks in developing countries outperform their domestic bank counterparts. It is therefore interesting to examine whether the same is applicable to the Islamic banking sector. Second, we compute a battery of DEA-based parametric and non-parametric tests to examine the difference in the efficiency of the Malaysian Islamic banking sector between the pre and post-entry periods. During both periods, the efficiency scores of the De Novo and the incumbent banks will be compared. By doing so, we would be able to shed some light on the sources of inefficiency in the Malaysian Islamic banking sector in general, differentiate between the De Novo and the incumbent banks' efficiency scores, and assess the impact of foreign banks entry on the efficiency of the incumbent banks. In undertaking the study, we have gathered information from the yearly financial statements of the two full-fledged domestic Islamic banks, three full-fledged foreign Islamic banks, 11 domestic IBS (Islamic banking scheme) banks, and four foreign IBS banks for the period 2001 to 2008. The empirical findings from this study suggest that the domestic banks have been relatively more efficient than their foreign and De Novo bank counterparts, while the De Novo banks have been the least efficient banking groups. The results indicate that the Malaysian Islamic banking sector has exhibited a lower level of efficiency during the post-entry of the De Novo banks period. The findings from the study should interest not only the managers of the banks, but numerous stakeholders such as the central banks, bankers associations, governments, and other financial authorities.